Drypetes aetoxyloides - Tanggaraju, S.; Felix, E. C.; Damit, A.; Khoo, E.; Matusin, Dg Ku Rozianah, M.; Colin Ruzelion Maycock; Mohd Yusof, Nur Adillah, M.Y.; Nilus, R.; Sugau, J.; Tsen, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Drypetes aetoxyloides is a small tree recorded from Luhan in Kinabalu Park. To date, the estimated area of occupancy (AOO) and extent of occupancy (EOO) are both 4 km2 respectively. The species is recorded to occur on hillside of primary forest with brown soil with an altitude of 1,350 m, therefore the most plausible threat that could affect the population would be the climate change. Hence, it is assessed as Vulnerable as if the species is subject to climate extremes it could be Critically Endangered or Extinct in the near future. Drypetes aetoxyloides is endemic to Sabah, Malaysia. It is restricted to Luhan in Kinabalu Park and was recorded to occur at 1,350 m.